Bagasse‐derived Carbon‐supported Ru nanoparticles as Catalyst for Efficient Dehydrogenation of Ammonia Borane. Issue 8 (22nd June 2020) - Cheng, Wei; Zhao, Xue; Luo, Wenxiu; Zhang, Yun; Wang, Yi; Fan, Guangyin
Abstract: Recently, metal nanoparticles (NPs) have been investigated widely as heterogeneous catalysts in the hydrolysis of ammonia borane (AB). However, the method is severely challenged by the dispersion and particle size of metal NPs, and needs efficient carbon materials as supports. Herein, we describe a facile two‐step synthesis strategy that takes advantage of hydrothermal synthesis and solid‐phase carbonization to fabricate N‐doped bagasse‐derived carbon materials (BC‐hs). The Ru particles can disperse well on the BC‐hs carbon matrix to form Ru/BC‐hs catalyst. It is found that the Ru/BC‐hs catalyst, under optimized conditions (3.5 wt% Ru loading), shows a high performance for the catalytic dehydrogenation of AB, with a TOF of 354 mol H2 (molRu min) −1 . The high catalytic performance of Ru/BC‐hs may be ascribed to the large surface area of BC‐hs (2250 m 2 /g) with abundant surface nitrogen and oxygen species, and more catalytically active Ru atoms are provided with the fine‐grained and uniformly distributed Ru NPs. This study exhibits a universal method to design and prepare high‐performance dehydrogenation catalysts, in which metal NPs are supported on biomass‐derived carbon from a highly recyclable and available plant. Abstract : A bagasse‐derived carbon (BC‐hs) material with a large surface area (2250 m 2 /g) and abundant surface nitrogen and oxygen species was obtained by a consecutive hydrothermal treatment and solid carbonation. The in‐situ formation of Ru/BC‐hs with ultrasmall and uniformly dispersed Ru NPs (1.4 nm) provide more catalytically active atoms for AB hydrolysis, achieving a high performance with a TOF of 354 mol H2 (molRu min) −1 .